Enthusiasm emotional practices of conviction in modern Germany - Scheer, Monique 1967- (Oxford University Press, 2020)
Enthusiasm is desirable, yet dangerous. More than just affective intensity, it entails belief. Combining historical and ethnographic methods, this text explores different styles of religious enthusiasm in Modern Germany, inflected by historical traditions and social milieus, in an effort to understand the modern ambivalence toward this feeling
Includes bibliographical references and index
This edition also issued in print: 2021
Keywords: Geschichte 1800-2000; Protestantism / Germany / History / 19th century; Experience (Religion); Enthusiasm / Religious aspects; Kultur; Enthusiasmus; Protestantismus; Deutschland